Effect of calcination induced phase transition on the photocatalytic hydrogen production activity of BiOI and Bi5O7I based photocatalysts - Chang, Chi-Jung; Chen, Ying-Chen; Tsai, Zheng-Ting (International journal of hydrogen energy, 2022)
Flower-like BiOI and Bi5O7I photocatalysts were synthesized by a microwave-assisted solvothermal process and then calcined at various temperatures. The effects of calcination temperature on the phase structure, crystal property, morphology, color, optical property, and activity of the photocatalysts were investigated. As the calcination temperature increased, a blue shift was observed in the diffuse reflection spectra and the band gap increased. After the calcination treatment at 500 °C, the XRD, Raman spectra, and TEM results confirmed that BiOI transformed to Bi5O7I. Although flower-like microspheres still existed, the shapes of building blocks changed from lamellar nanoplates to thick twisted stripes when the BiOI transformed to Bi5O7I. BiOI with a calcination treatment at 300 °C exhibits an improved H2 production activity of 1373 μmol g−1 h−1. The XRD spectra reveal that the B-400 photocatalyst was a Bi5O7I-rich and BiOI-deficient composite material. Fewer Bi5O7I–BiOI interfaces and lower light absorption may be the reasons why the B-400 photocatalyst with Bi5O7I–BiOI compositions did not exhibit higher activity than B-300 (pure BiOI) and B-500 (pure Bi5O7I) photocatalysts. •BiOI and Bi5O7I were synthesized by a microwave solvothermal process and calcination.•As BiOI transformed to Bi5O7I, there are changes in morphology, XPS, DRS, XRD, and Raman spectra.•Building blocks of microflowers changed from lamellar to twisted stripes as BiOI transformed to Bi5O7I.•B-300 (pure BiOI) exhibits a higher H2 production activity (1373 μmol g−1 h−1) than B-400 (Bi5O7I–BiOI).•Fewer Bi5O7I–BiOI interfaces and lower light absorption lead to lower activity of B-400.